2013
DOI: 10.1039/c3cc45879b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of allylboronates by Pd-catalysed borylative cyclisation of dienynes

Abstract: Reaction of a variety of dienynes with bis(pinacolato)diboron catalysed by Pd bis(trifluoroacetate) affords allylic boronates containing five or six membered carbo- or heterocycles, by concomitant formation of one C-C and one C-B bonds. Resulting allylboronates can be employed for a variety of subsequent transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Polyunsaturated derivatives were also suitable substrates for Pd‐catalyzed borylative cyclization. Dienynes derived from 1,6‐enynes by formal addition of a second alkene conjugated to the existing one reacted under catalysis by Pd(TFA) 2 to give exocyclic allylboronates (Scheme ) . These products could have been expected according to the reaction outcome observed for simple 1,6‐enynes described above.…”
Section: Borylative Cyclization Involving the Formation Of C–c Bondsmentioning
confidence: 91%
“…Polyunsaturated derivatives were also suitable substrates for Pd‐catalyzed borylative cyclization. Dienynes derived from 1,6‐enynes by formal addition of a second alkene conjugated to the existing one reacted under catalysis by Pd(TFA) 2 to give exocyclic allylboronates (Scheme ) . These products could have been expected according to the reaction outcome observed for simple 1,6‐enynes described above.…”
Section: Borylative Cyclization Involving the Formation Of C–c Bondsmentioning
confidence: 91%
“…[12d] Using the same catalyst, borylative cyclization of 1,3-dien-8-ynes was reported to give allylic boronates having five or six membered carboor heterocycles. [30] Later they also demonstrated that changing the ligand can control the reaction outcome. [11] An allylic carbonate containing enynes gave decarboxylative borylation products (allylboronates) when Pd(OAc) 2 was used as a catalyst and NHC as a ligand (IMes = 1,3-bis(2,4,6-trimethylphenyl)-imidazolium), whereas replacing the NHC with PCy 3 gave borylative cyclization products (alkenylboronates).…”
Section: Palladium-catalyzed Hydroboration Of Enynesmentioning
confidence: 99%
“…In 2012, Cárdenas and co‐workers reported Pd(TFA) 2 (TFA=trifluoroacetate) catalyzed borylative cyclization of 1,7‐enynes which led to formation of six‐membered rings via 1,8‐hydroboration followed by cyclization . Using the same catalyst, borylative cyclization of 1,3‐dien‐8‐ynes was reported to give allylic boronates having five or six membered carbo‐ or heterocycles . Later they also demonstrated that changing the ligand can control the reaction outcome .…”
Section: Catalytic Hydroboration Of Enynesmentioning
confidence: 99%
“…Borylative cyclization of 1,6-enynes containing a second olefinic bond with bis(picolinato)diboron in the presence of a Pd catalyst and MeOH gives five-membered carbocycles (Scheme 28). 76 The reactions are suggested to proceed via η 3 -allyl complexes, leading to products with boron at the terminal position.…”
Section: Cyclization Of Dienynes and Enediynesmentioning
confidence: 99%